2022
DOI: 10.4155/fdd-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 as a novel target in immunology: moving away from typical antagonists

Abstract: CXCR4 has been a target of interest in drug discovery for numerous years. However, so far, most if not all studies focused on finding antagonists of CXCR4 function. Recent studies demonstrate that targeting a minor allosteric pocket of CXCR4 induces an immunomodulating effect in immune cells expressing CXCR4, connected to the TLR pathway. Compounds binding in this minor pocket seem to be functionally selective with inverse agonistic properties in selected GPCR signaling pathways (Gi activation), but additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…The closely matched spacings between the side chains of D262 6 58 . and E288 7 39 . residues and the cyclam rings therefore appears be the main binding determinant of AMD3100 and other bicyclam analogues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The closely matched spacings between the side chains of D262 6 58 . and E288 7 39 . residues and the cyclam rings therefore appears be the main binding determinant of AMD3100 and other bicyclam analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Each of the two positively charged cyclam rings of AMD3100 45 is stabilized electrostatically by an acidic side chain pointed toward the center of the ring; the cyclam moiety closer to the extracellular side interacts with D262 6 58 . while the cyclam proximal to the transmembrane core interacts with E288 7 39. .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same vein, we have recently shown that CXCR4 can exist in different conformations at the cell surface, some of which are used by particular HIV-1 strains but not by CXCL12 [ 43 ]. Similarly, some CXCR4 ligands induce different signaling responses compared to CXCL12, presumably owing to different interaction sites in the receptor binding pocket [ 44 ]. These data therefore suggest that it is conceivable to inhibit some functions of CXCR4 while preserving others.…”
Section: Introductionmentioning
confidence: 99%